Estrategias metodológicas para el proceso de enseñanza-aprendizaje de la biología a nivel universitario - Chuquimarca Espinoza, Leiddy Elizabeth (2024)
The methodological strategies constitute an essential element in the teaching-learning process, being able to propitiate the real significant learning in biology, besides rescuing the skills, abilities and values, which are developed during this process. The objective of this research was to analyze the contribution of the methodological strategies developed by teachers in the teaching-learning process of biology in the career of Pedagogy of Experimental Sciences-Chemistry and Biology at “Universidad Nacional de Loja” in the period 2023. This research was carried out under a qualitative, descriptive, documentary and field approach. Two techniques were used to obtain data: observation, with its instrument: the observation form; and the interview with its respective guide of questions directed to the teachers of Biology I, Biology II, Botany, and Zoology. The results obtained showed that the methodological strategies applied in the biology course such as PBL (Problem Based Learning), the flipped classroom, discovery learning, collaborative learning, cooperative learning and experimentation have a relevant influence on the teaching-learning process, which allows students to develop their talents and skills in a holistic way to ensure meaningful and lasting learning. Keywords: Methodological strategies; teaching; learning; Biology